Impact of ethical behavior on syndicated loan rates - Kim, Moshe (My University, 2016)
This paper shows that borrowers’ ethical behavior leads lending banks to loosen financing conditions when setting loan rates. We advance the banking literature by stressing that the previous financing loosening is enhanced when there is similarity of lenders and borrowers along their ethical domain given that such similarity brings about familiarity and trust in non-opportunistic behavior between them, thereby contributing to lower information frictions. Unique data composed of 12,545 syndicated loan facilities from 19 countries for the period 2003–2007 indicate a 24.8% reduction in the mean spread associated with an increase of one standard deviation in the degree of borrowers’ ethical behavior from its mean value. Such reduction is enhanced to 37.6% when lenders also behave in an ethical way. Results withstand a battery of robustness tests including the use of alternative databases that capture the effect of the 2008 financial crisis, financing alternatives such as equity financing as well as nonparametric estimations.
Keywords: Préstamos; Ethical behavior; Loan rates